Religion and politics under capitalism: a humanistic approach to the terminology - Arvidsson, Stefan (Routledge studies in religion, 2019)
Totalitarianism and political religion -- Mythic politics and the masses -- Excursion: on comparison -- Liberalism and capitalist religion -- Secular age, idealist scholarship -- "Everything religion" and the capitalist framework -- A humanistic view on religion -- Basic definitions -- Relating modern religions and political ideologies.